Path planning for the Platonic solids on prescribed grids by edge-rolling - Lam, Ngoc Tam; Howard, Ian; Cui, Lei (PUBLIC LIBRARY SCIENCE, 2021)
The five Platonic solids-tetrahedron, cube, octahedron, dodecahedron, and icosahedron- have found many applications in mathematics, science, and art. Path planning for the Platonic solids had been suggested, but not validated, except for solving the rollingcube puzzles for a cubic dice. We developed a path-planning algorithm based on the breadth-first-search algorithm that generates a shortest path for each Platonic solid to reach a desired pose, including position and orientation, from an initial one on prescribed grids by edge-rolling. While it is straightforward to generate triangular and square grids, various methods exist for regular-pentagon tiling. We chose the Penrose tiling because it has five-fold symmetry. We discovered that a tetrahedron could achieve only one orientation for a particular position.